Konsep Uang: Ekonomi Islam VS Ekonomi Konvensional - Santi Endriani (Anterior Jurnal, 2015)
In Islamic economics, the concept of money is very clear that money is a medium of exchange in muamalah, instead of capital (commodities). That money is objected that are approved by the public as an intermediary tool to hold the exchange or trade. Differences concept of money in Islamic and conventional economics are on the money that is not identical to the capital, the money is public goods, capital is private goods, money is a flow concept, and capital is a stock concept in the concept of money in Islam. While the conventional concept of money in the currency identified with capital money (capital) are private goods. Money (capital) is a flow concept for Fisher, and money (capital) is a stock concept for Cambridge School.